The immediate alteration of cerebellar Glx/GABA and cerebello-thalamo-cortical connectivity in patients with schizophrenia after cerebellar TMS - Chenyang Yao; Youjin Zhao; Qian Zhang; Ziyuan Zhao; Kai Ai; Bo Zhang; Su Lui (Schizophrenia)
Abstract Cerebellar dysfunction is a key aspect of schizophrenia, with the cerebello-thalamo-cortical (CTC) hyperconnectivity serving as a neural signature. Abnormalities in gamma-aminobutyric acid (GABA) and glutamate + glutamine (Glx) levels also contribute to this pathology. Transcranial magnetic stimulation (TMS) applied to the cerebellum shows potential in alleviating schizophrenia symptoms, possibly by modulating functional connectivity or neurotransmitter levels. This study aims to explore the immediate effects of cerebellar TMS on CTC circuitry and neurotransmitter levels to elucidate its therapeutic mechanisms in schizophrenia.The study involved 19 stable schizophrenia patients and 26 healthy controls, diagnosed according to DSM-V criteria and assessed for symptom severity using the Positive and Negative Syndrome Scale (PANSS). MRI scans were conducted pre- and post-TMS to detect changes in CTC functional connectivity, GABA, Glx, and Glx/GABA. Linear Mixed-Effects Model (LMEM) and two-sample tests were employed to analyze changes in these variables from baseline to post-TMS. Pearson’s correlation analysis was conducted to examine the relationships among these variables and their association with PANSS scores. Mediation analyses were employed to investigate whether GABA and/or Glx serve as potential mediators of CTC hyperconnectivity in patients with schizophrenia. Schizophrenia patients exhibit CTC hyperconnectivity, which remains at a relatively stable level after cerebellar TMS. Compared to healthy controls, schizophrenia patients have significantly higher cerebellar GABA levels, and cerebellar GABA has a significant mediation effect on CTC hyperconnectivity in patients. The Glx/GABA ratio was associated with the severity of clinical symptoms in patients, and cerebellar TMS partially normalized this ratio. Our findings demonstrate that aberrant cerebellar GABA levels contribute to CTC hyperconnectivity in schizophrenia. Additionally, our study shows that cerebellar TMS can increase Glx levels in schizophrenia patients, leading to the normalization of the Glx/GABA ratio, which may contribute to the therapeutic effects of TMS in schizophrenia.